The UCD nanosafety workshop (03 December 2018): towards developing a consensus on safe handling of nanomaterials within the Irish university labs and beyond – a report. Issue 6 (3rd July 2019) - Stuttgen, Vivien; Giffney, Hugh E.; Anandan, Ayana; Alabdali, Anwar; Twarog, Caroline; Belhout, Samir A.; O′Loughlin, Mark.; Podhorska, Lucia; Delaney, Colm; Geoghegan, Niamh; Mc-Fadden, Jessica; Alhadhrami, Nahlah A.; et al.
Abstract: Careful handling of the nanomaterials (NMs) in research labs is crucial to ensure a safe working environment. As the largest university in Ireland, University College Dublin (UCD) has invested significant resources to update researchers working with NMs. Due to sizes often <100 nm, the NMs including nanoparticles, harbor unprecedented materialistic properties, for example, enhanced reactivity, conductivity, fluorescence, etc. which albeit conferring the NMs an edge over bulk materials regarding the applied aspects; depending on the dose, also render them to be toxic. Thus, a set of regulatory guidelines have emerged regarding safe handling of the NMs within occupational set-ups. Unfortunately, the current regulations based on the toxic chemicals and carcinogens are often confusing, lack clarity, and difficult to apply for the NMs. As a research-intensive university, a diverse range of research activities occur within the UCD labs, and it is difficult, at times impossible, for the UCD Safety, Insurance, Operational Risk & Compliance (SIRC) office to develop a set of common guidelines and cater throughout all its labs conducting research with the NMs. Hence, a necessity for dialog and exchange of ideas was felt across the UCD which encouraged the researchers including early stage researchers (e.g. PhDs, Postdocs) from multiple schools to participate in a workshop held on the 03 December 2018. The workshop tried to follow a pragmatic approach, where apart from discussing both the in vitro and in vivo scenarios, practical cases simulating situations faced frequently in the labs were discussed. This report summarizes the findings made during the workshop by this emerging critical mass in UCD.